Research trends on business strategy formulation: A systematic literature review and bibliometric analysis - Rahman, Arif; Dewayana, Triwulandari Satitidjati; Maulidya, Rahmi; Arafah, Willy (Universitas Sultan Ageng Tirtayasa, 2025)
Survival in the modern technological landscape demands an effective competitive strategy for every industry, and the offset printing sector is no exception. This study explores trends and future research opportunities in strategy formulation within this specific industry. We utilized a Systematic Literature Review (SLR) methodology complemented by bibliometric analysis. Relevant literature was gathered from sources such as Sciencedirect.com and Publish or Perish version 8, using keywords like